Реконструкция природной среды обитания человека на позднепалеолитической стоянке у с. Каменка - Герасименко, Н.П.; Снежко, И.А. (My University, 2012)
N. Gerasymenko, I. Snizhko. Paleoenvironmental Reconstruction of the Upper Paleolithic Site Near Kamyanka Village Paleoenvironmental reconstruction is an important part of the multidisciplinary study of the Upper Paleolithical sites. Pollen analysis is one of the prospective approaches for this purpose. From the excavation wall of the site near Kamyanka village, which technological complex belongs to the eastern Epi-Gravettian, 8 samples were taken and palynologically studied (two of them from the cultural layer). The obtained pollen spectra show that at the time of the site functioning, this area was located in the subperiglacial steppe. The climate was much colder and drier than that of today. The vegetation cover was sparser, poorer and more uniform in composition. As the site was situated in the river valley, it was surrounded by light woods and meadows from grasses and mesophytic herbs.
Keywords: the Paleolith; the site near Kamyanka village; pollen analysis; palaeovegetation